The Appliction of Modified Gausse-Newton Method for Improving Accuracy of Regime Parameters State Estimation and Control Action Adjusment in The Centralized Emergancy Control System; Relay Protection and Automation (RPA 2020) - Batseva N. L. Natalya Lenmirovna (2020, 2020)
Title screen